Scale Effects of the Relationships between 3D Building Morphology and Urban Heat Island: A Case Study of Provincial Capital Cities of Mainland China. (27th November 2020) - Qiao, Zhi; Han, Xiping; Wu, Chen; Liu, Luo; Xu, Xinliang; Sun, Zongyao; Sun, Wei; Cao, Qian; Li, Linwan
Abstract : In the process of rapid urbanization, urban heat island (UHI) effect has been showing more and more significant impacts on human well-being. Therefore, a more detailed understanding of the impact of three-dimensional (3D) building morphology on UHI effect across a continuum of spatial scales will be necessary to guide and improve the human settlement.This study selected 31 provincial capital cities of mainland China to analyze the impacts of the 3D building morphology, including the number, area, height, volume, and the surface area of the buildings, on the land surface temperature (LST). By exploring how the influence of 3D building morphology on LST changes with the increase of spatial scale (between 0 and 600 m radii), this study finally recognized which 3D building morphology index is the most significant index affecting LST in different cities, and which spatial scale these 3D building morphology indexes have the most significant impact on LST. The results showed that the building area is the most important 3D building morphology parameter affecting the LST, while the building height has the slightest influence on the LST. These effects are more significant in the spatial scale of 150 m–540 m, and the spatial scale increases with the increase of building areas in developed cities. These results highlight the necessity of considering fine-grained management in the governance and alleviating of the urban thermal environment through urban planning and urban renewal strategies.